Superficial temporal artery waveform - Chan, Chen Leong. (2011)
This project is base on the study of using the superficial temporal arterial (STA) waveform to compute an index through experiments to find out if the STA index will increase proportionally as a person’s age increase with the hypothesis that older people will have artery blockage due to accumulated fatty materials or plaque. The index form will be of great help in early detention of stroke. Fifteen cleaners of the higher age group range from forty-eight to seventy-three years old and nineteen students from Nanyang Technological University of an average twenty-five years old have volunteer to take part in the experiment. The readings collected will be added to the database which had readings that have been collected for the past two years. Four types of method are used to compute four different types of STA index.